Scalable fabrication of graphene-assembled multifunctional electrode with efficient electrochemical detection of dopamine and glucose - Ji, Xiaodong; Zhao, Xin; Zhang, Zixin; Si, Yunfa; Qian, Wei; Fu, Huaqiang; Chen, Zibo; Wang, Zhe; Jin, Zhugen; He, Daping (Springer, 2023)
Conventional glassy carbon electrodes (GCE) cannot meet the requirements of future electrodes for wider use due to low conductivity, high cost, non-portability, and lack of flexibility. Therefore, cost-effective and wearable electrode enabling rapid and versatile molecule detection is becoming important, especially with the ever-increasing demand for health monitoring and point-of-care diagnosis. Graphene is considered as an ideal electrode due to its excellent physicochemical properties. Here, we prepare graphene film with ultra-high conductivity and customize the 3-electrode system via a facile and highly controllable laser engraving approach. Benefiting from the ultra-high conductivity (5.65 × 105 Sm−1), the 3-electrode system can be used as multifunctional electrode for direct detection of dopamine (DA) and enzyme-based detection of glucose without further metal deposition. The dynamic ranges from 1–200 µM to 0.5–8.0 mM were observed for DA and glucose, respectively, with a limit of detection (LOD) of 0.6 µM and 0.41 mM. Overall, the excellent target detection capability caused by the ultra-high conductivity and ease modification of graphene films, together with their superb mechanical properties and ease of mass-produced, provides clear potential not only for replacing GCE for various electrochemical studies but also for the development of portable and highperformance electrochemical wearable medical devices.
Keywords: graphene film; ultra-high conductivity; multifunctional electrode; point-of-care diagnosis; wearable medical devices